FAKTOR-FAKTOR YANG MEMPENGARUHI INTEGRITAS LAPORAN KEUANGAN DENGAN KOMITE AUDIT SEBAGAI VARIABEL MODERASI (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2016-2018) - Ningsih Fitri Lia; Kamaliah Kamaliah; Haryani Eka (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
The purpose of this study was to determine the effect of KAP reputation, audit tenure and company size on the integrity of financial statements with the audit committee as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange (BEI). The data used in this research is secondary data, namely the Annual Report. The population in this study are all manufacturing companies listed on the IDX for the 2016-2018 period. The number of samples in this study were 210 samples for 3 years using purposive sampling. The analysis technique in this study used moderated regression analysis (MRA) and was performed using SPSS version 25. The results of this study indicate that the KAP reputation, audit tenure and company size affect the integrity of financial statements with significant values of 0.032, 0.002 and 0.002. This study finds evidence that the audit committee is able to moderate the effect of audit tenure on the integrity of financial statements with a significant value of 0.016. However, this study found that the audit committee was unable to moderate the effect of KAP reputation and company size on the integrity of financial statements with significant values of 0.299 and 0.055.Keywords: KAP Reputation, Audit Tenure, Company Size, audit committee, Integrity of Financial Statements